The Effect of HK-1001 Pharmacopuncture on Hyperlipidemia Induced Rats - Hong Kwon-Eui; Kim Ji-Nam (Korean Pharmacopuncture Institute, 2008)
Objective&Methods : The purpose of this study is to observe the effects of HK-1001 Pharmacopuncture at GB34(Yangleungchean) on hyperlipidemia in rats. The author performed several experimental items to analyze the levels of various components and enzymes in serum, urine and liver, as well as the histological changes of liver and aorta. Results : 1. HK-1001 Pharmacopuncture infusion solution increased the cell viability rate, DPPH radical scavenging activity and HMG-CoA reductase inhibition rate in rat liver cells. 2. The levels of total cholesterol, free cholesterol, LDL-cholesterol, phospholipid in serum and AI(atherogenic index) were decreased, and the ratio of HDL to TCL(HDL/TCL) and the level of TG in serum were increased as compared with those of the control group. 3. In the HK-1001 group, serum GOT was significantly lower than those of the HG group and the saline group, and serum ALP was significantly higher than that of the HG group. 4. Hepatic GSH and catalase activities were significantly increased as compared with those of the saline group. Conclusion : From the above results, it is suggested that HK-1001 Pharmacopuncture at GB34 has a therapeutic effect on hyperlipidemia.